HEALING WITH THE USE OF TITANIUM THREADS OF CONTROLLED BONE RESORPTION - Rizaev Elyor Alimdjanovich; Buzrukzoda Javokhirkhon Davron (Journals Park Publishing, 2023)
In this work, a comparative assessment of postoperative healing and the state after treatment with non-absorbable titanium threads and a resorbable collagen membrane after controlled bone resorption was carried out. Under observation were 50 patients who applied to the private clinic "Dr. Ilkhom" in Samarkand about the need for orthopedic treatment. Depending on the method of treatment, they were divided into 2 groups. Operations were performed on both the upper and lower jaws. At the same time, regenerative intervention was carried out in combination with an open sinus lift procedure. The length of the defects ranged from one to five missing teeth. When analyzing the healing of soft tissues in members of both groups in the early postoperative period, according to the ECI index, the indicators of the first group were 1.6±0.86 points, and the second group - 1.76±1.1 points.
Keywords: controlled bone resorption (CBR), titanium threads, collagen membrane, orthopantomography (OPTG), attached, keratinized gingiva.